Encanterias in art/education research: other ways of thinking/doing/feeling about teaching in visual arts (Revista Apotheke, 2024)
The visual essay "Encanterias in Research in Art/Education: Other Ways of Thinking/Doing/Feeling Teaching in Visual Arts" proposes an inventive approach to arts-based educational research, incorporating the principles of Dissenting Art/Education and the methodology of encanterias . Investigating the concept of "encanterias", the essay seeks to offer alternative perspectives to rethink and reconceptualize teaching practice in visual arts. Through visual language, the work presents different ways of approaching teaching, integrating cultural, aesthetic and pedagogical elements in a unique way. The proposal aims to inspire critical reflection on the transformative possibilities that encanterias, within the context of Dissident Art/Education, can offer to the field of Art/Education, promoting a deeper connection between artistic practice, research and teaching experience. The images present in this essay present research from course completion work by students of the Degree in Visual Arts at the Federal University of Amapá, under the guidance of Prof. Dr. Fábio Wosnaik.
Keywords: encanterias methodology; dissenting art/education; teacher training in visual arts